The Influence of Personality Traits, Rationality, And Self-Efficacy Towards Decision-Making Styles Among Technical Trainees - Ahmad, Nor Shafrin; Mohamad Sulaiman, Ahmad Amin (Journal of Technical Education and Training, 2022)
One of the qualities that employers often observe in potential graduates is the ability to display soft skills such as decision-making. It is suspected that some personality traits, cognitive domains, and efficacy have some effects on individual decision-making. Such awareness is expected to help technical trainees establish improved decision-making styles later that could have a positive professional impact. The aim of this study is to identify the domain of personality traits, rationality tendencies, self-efficacy and the combination of predictors that affect the decision-making style of trainees in technical training institutions. This study was conducted using a survey quantitative design as the data collection tool. A population of 740 full-time trainees in electrical engineering from eight public technical training institutes were selected and 591 were identified using a stratified random sampling technique. Data was collected using the Big Five Inventory (BFI), Rational-Experiential Inventory (REI), General Self-Efficacy Scale (GSES) and Maximization Scale. Based on multiple regression analysis, it is concluded that self-efficacy is the strongest predictor affecting decision-making styles among trainees at technical training institutions, as opposed to rationality, personality traits or a combination of predictors. This implies that self-efficacy has a profound effect on decision-making style. It could lead the trainee to make decisions based on his own experiences, rather than abiding by safety rules and standard operating procedures. The trainees should realize decisions solely based on past convictions and experiences could cause detrimental effects on employers and themselves.